Formulation of nanopesticide with graphene oxide as the nanocarrier of pyrethroid pesticide and its application in spider mite control. Issue 57 (9th November 2021) - Gao, Xiaoduo; Shi, Fengyu; Peng, Fei; Shi, Xuejuan; Cheng, Caihong; Hou, Wenlong; Xie, Haicui; Lin, Xiaohu; Wang, Xiuping
Abstract : Nanopesticides with controlled release can achieve more effective utilization of pesticides. Abstract : Nanopesticides with controlled release can achieve more effective utilization of pesticides. Here, to enhance the adsorption of pesticides onto the target organisms, the formulation of pesticides with temperature-responsive release was proposed by combing graphene oxide (GO) and existing pyrethroid pesticides (cyhalothrin, bifenthrin and fenpropathrin). Pesticides were loaded onto GO nanosheets as a carrier via a simple physisorption process, and the GO–pesticide nanocomposites exhibited temperature-responsive release and excellent storage stability, which are of vital importance to the practical application. Furthermore, we assessed the bioactivity of the GO–pesticide nanocomposites against spider mites ( Tetranychus urticae Koch) indoors and in the field. As a result, GO–pesticide nanocomposites had many folds higher bioactivity than individual pesticides, and could be adsorbed on the cuticle of T. urticae and surface of bean leaves with highly uniform dispersibility. The easy preparation and higher bioactivity of GO–pesticide nanocomposites indicate their promising application potential in pest control and green agriculture.